Comparison of different culinary processing on the nutrient characteristics of mrigal (Cirrhinus cirrhosus) from the Loktak Lake in Manipur, northeast India - Heikham DAYAMI; Chungkham SAROJNALINI; Bronson Kumar KHANGEMBAM (Notulae Scientia Biologicae)
Cirrhinus cirrhosus is a popular and important food fish in northeastern India, rich in high-quality protein, essential amino acids, ω-3 fatty acids, minerals like phosphorous and iron and fat-soluble vitamins (A and D). However, different cooking processes may affect the characteristics and bioavailability of most of these nutrients. With increasing consumers' awareness of nutrient preservation, an assessment of the common cooking processes is necessary to select the best cooking methods for the maximal preservation of precious nutrients. This study comprehensively investigated the proximate composition, amino acid and fatty acid profiles, lipid quality indices, vitamins and mineral composition of C. cirrhosus before and after common culinary processing, viz., steaming in water, microwave oven cooking, oil frying and currying. The results indicated significant (p < 0.05) changes in all the nutrient parameters after cooking. Protein, lipid and ash increased after all the cooking methods, corresponding to moisture reduction. Eicosapentaenoic acid (EPA, C20:5n-3) and docosahexaenoic acid (DHA, C22:6 n-3) decreased 36-43% and 37-53%, respectively, after frying and currying, while microwaving increased the total PUFAs (by 12.03%). The fatty acid composition, lipid quality indices, and mineral composition changes were more significantly visible in oil frying and currying. Comparatively, steaming and microwaving resulted in lesser nutrient quality deterioration than the rest. In summary, it may be concluded that the nutrient characteristics of mrigal undergo changes due to various thermal-induced reactions during the cooking process, and hence, cooking under controlled conditions may be recommended for preserving these nutrients.